Molecular imaging of myocardial infarction with Gadofluorine P – A combined magnetic resonance and mass spectrometry imaging approach. Issue 4 (April 2018) - Lohöfer, Fabian; Hoffmann, Laura; Buchholz, Rebecca; Huber, Katharina; Glinzer, Almut; Kosanke, Katja; Feuchtinger, Annette; Aichler, Michaela; Feuerecker, Benedikt; Kaissis, Georgios; Rummeny, Ernst J.; Höltke, Carsten; et al.
Abstract: Background: Molecular MRI is becoming increasingly important for preclinical research. Validation of targeted gadolinium probes in tissue however has been cumbersome up to now. Novel methodology to assess gadolinium distribution in tissue after in vivo application is therefore needed. Purpose: To establish combined Magnetic Resonance Imaging (MRI) and Mass Spectrometry Imaging (MSI) for improved detection and quantification of Gadofluorine P deposition in scar formation and myocardial remodeling. Materials and methods: Animal studies were performed according to institutionally approved protocols. Myocardial infarction was induced by permanent ligation of the left ascending artery (LAD) in C57BL/6J mice. MRI was performed at 7T at 1 week and 6 weeks after myocardial infarction. Gadofluorine P was used for dynamic T1 mapping of extracellular matrix synthesis during myocardial healing and compared to Gd-DTPA. After in vivo imaging contrast agent concentration as well as distribution in tissue were validated and quantified by spatially resolved Matrix-Assisted Laser Desorption Ionization (MALDI) MSI and Laser Ablation – Inductively Coupled Plasma – Mass Spectrometry (LA-ICP-MS) imaging. Results: Both Gadofluorine P enhancement as well as local tissue content in the myocardial scar were highest at 15 minutes post injection. R1 values increased from 1 to 6 weeks after MI (1.62 s −1 vs 2.68 s −1, p = 0.059) paralleled by an increase in Gadofluorine P concentration in the infarct from 0.019 mM at 1 week to 0.028 mM at 6 weeks (p = 0.048), whereas Gd-DTPA enhancement showed no differences (3.95 s −1 vs 3.47 s −1, p = 0.701). MALDI-MSI results were corroborated by elemental LA-ICP-MS of Gadolinium in healthy and infarcted myocardium. Histology confirmed increased extracellular matrix synthesis at 6 weeks compared to 1 week. Conclusion: Adding quantitative MSI to MR imaging enables a quantitative validation of Gadofluorine P distribution in the heart after MI for molecular imaging.